Female Fatherlands: Women of Letters, Greek Patriotism and the 1821 Revolution - Papalexopoulou, Elisavet (Historein, 2023)
This article examines the patriotic discourses of a few female thinkers who were connected with the Greek cause, before and during the Greek Revolution. It examines how they understood Greece and Europe as social, political, geographical and revolutionary spaces and how they understood the gendered character of the war. It seeks to challenge traditional localities of the Greek Revolution by including women who lived in areas that were not encompassed by the Greek nation-state after its inception and did not necessarily use the Greek language in their writings.